On Inspecting the Hierarchical Inter-Relationships amongst the Various Barriers to Successful Adoption of Various Fermented Food Products - Aggarwal, V. K.; Aggarwal, Remica (Current Perspectives in Agriculture and Food Science Vol. 7, 2024)
In underdeveloped and developing countries, due to poverty, fermentation is one of the most widely used preservation methods. It not only allows extending the shelf life of food, but also brings other benefits, including inhibiting the growth of pathogenic microorganisms, improving the product digestibility, and can be a valuable source of functional microorganisms. Hence, fermented foods and beverages are becoming a part of the traditional diet as well as playing a role in the nutrition of people around the world. This chapter inspects the hierarchical interrelationship amongst the various barriers behind successful adoption of various category fermented food products based on creation of matrices as per VAXO technique mentioned in Interpretive Structural Modeling Methodology [ISM] methodology.